Evaluation of tribothermal effectiveness of TiAlN-based bilayer coatings in cutting fiber-reinforced polymers. (November 2016) - Mkaddem, Ali; Zeramdini, Bessam; El Mansori, Mohamed; Mezlini, Salah
Abstract: This work addresses the tribological reliability of TiAlN-based PVD coatings face to TiN-based CVD coating in cutting FRP. Wear and linear pin-on-plate tests were conducted on both glass/epoxy and carbon/epoxy composites for investigating wear progression and apparent friction, respectively. The TiAlN location shows great role in controlling wear upon PVD coatings. While abrasion was found dominating the wear mechanisms upon the flank face irrespective to coating type, PVD coatings demonstrate better ability to dissipate severe cratering. Although the all coatings showed close behavior against carbon/epoxy, TiAlN/AlCrO coating revealed great vulnerability against glass/epoxy resulting in extended AlCrO layer failure. While wear substantially reduces the thermal conductivity, PVD coatings kept roughly better conductivities than CVD coating as for worn states. Highlights: Cutting tests were performed on GFRP and CFRP using TiAlN-based PVD coatings. Wear was addressed with regard to the location of TiAlN layer within the coating. Pin-on-plate tests led to analyze PVD-obtained friction maps vs . CVD-obtained ones. Effectiveness of PVD coatings to cutting GFRP and CFRP materials was discussed.